2001
DOI: 10.1111/j.1471-0528.2001.00097.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidural compared with general anaesthesia for caesarean delivery in conscious women with eclampsia

Abstract: Objective To compare retrospectively the outcome of caesarean section under epidural anaesthesia with that of general anaesthesia in ªstableº women with eclampsia. Design Retrospective review.Method Over the ®ve±year study period, there were 533 women with eclampsia and of these 66 women (12.4%), ful®lled the criteria of being`stable'. Of the 66 women, 37 received epidural, 27 general, and 2 spinal anaesthesia. Results There were no major complications with either general or epidural anaesthesia. Epidural anae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…However, not all studies held a similar view. Ajuzieogu et al [15], Moodley et al [21], and Santos and Birnbach [22] found similar neonatal outcomes irrespective of anesthesia administered. Laudenbach et al [23] on the other hand noted a higher risk of mortality in neonates in the spinal group compared to general and epidural anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…However, not all studies held a similar view. Ajuzieogu et al [15], Moodley et al [21], and Santos and Birnbach [22] found similar neonatal outcomes irrespective of anesthesia administered. Laudenbach et al [23] on the other hand noted a higher risk of mortality in neonates in the spinal group compared to general and epidural anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective randomized, multicenter study conducted by Visalyaputra S et al [8] concluded that SAB was safe for CS in patients with severe preeclampsia. The incidence and magnitude of hypotension following SAB for CS are lesser in patients with severe preeclampsia when compared with healthy parturients [9] as hypertension is not sympathetically mediated [10] in preeclampsia.…”
Section: Hypertensive Disorders Of Pregnancy Can Be Defined As Followsmentioning
confidence: 88%
“…Women who have had an eclamptic seizure but are fully conscious and co-operative, have a platelet count 4 100 6 10 9 l 71 and have received magnesium sulphate can undergo regional anaesthesia safely (Moodley et al, 2001). An incremental epidural technique was used in this case to allow haemodynamic stability during gradual establishment of the block.…”
Section: Discussionmentioning
confidence: 99%